Effect of apelin hormone on renal ischemia/reperfusion induced oxidative damage in rats - Bircan, Burak; Cakir, Murat; Kirbag, Sevda; Gul, Huseyin Fatih (Taylor & Francis Ltd, 2016)
Apelin is a peptide hormone defined as a ligand for G-protein clamped receptor (APJ) receptor. It is indicated in the literature both apelin and APJ are synthesized on the peripheral tissues including the renal tissues. Which roles does the apelin play on the renal tissue has not been completely illuminated yet. This study is designed to determine the possible protective effect of apelin-13 on the kidney I/R injury. Adult male Sprague-Dawley rats were used in this study. In the sham group, right kidneys of the animals were dissected. In the I/R group, right kidney was dissected and ischemia of 45min was performed, and then reperfusion was applied for 3h. In the treatment groups, three different doses of apelin were injected at the beginning of the ischemia unlike the I/R group. BUN, Cre, Na, K, Cl, total protein and albumin from serum samples were determined and TNF-, IL-1, IL-6, TAS and TOS parameters were read with ELISA reader. MDA, SOD, CAT and GSH-Px enzyme activations from renal tissues were measured. In comparison with the sham and I/R groups, while the serum BUN, CRE, CI and TNF- levels showed an increase in the groups on which the apelin-13 was applied, Na, total protein, albumin, TAS levels decreased. Serum TOS level of other groups showed an increase by comparison with the sham group. Our results showed that apelin-13 applied after I/R increased the antioxidant enzyme activity in a dose dependent manner, prevented the lipid oxidation and improved the renal functions.
Keywords: Antioxidant; apelin; APJ; ischemia-reperfusion; kidney; oxidative stress